Characteristics of surveillance systems for suicide and self-harm: A scoping review. - Aline Conceição Silva; Amanda Sarah Vanzela; Laysa Fernanda Silva Pedrollo; John Baker; José Carlos Marques de Carvalho; Carlos Alberto da Cruz Sequeira; Kelly Graziani Giacchero Vedana; José Carlos Pereira Dos Santos (PLOS Global Public Health)
Background Suicide is a complex public health issue. Surveillance systems play a vital role in identifying trends and epidemiologic needs, informing public health strategies, and tailoring effective context-based suicide prevention interventions. Aim To identify and summarise the characteristics of specific surveillance systems and general health behaviour that include data onsuicide and self-harm. Method A scoping review following the JBI recommendations and PRISMA-ScR guidelines identified 29 relevant studies on suicide and self-harm surveillance systems. A systematic search was performed on Cinahl, Embase, Lilacs-Latin American and Caribbean Health Sciences Literature, PubMed-US National Library of Medicine, Scopus, and Google Scholar. The eligibility criteria include papers that use qualitative, quantitative or mixed methods with no restrictions on time or language. The following papers were excluded regarding euthanasia and assisted suicide, as well as papers that did not explicitly describe suicide, self-harm, and surveillance systems. Two researchers independently screened the materials for eligibility and extracted data from the included studies. Data analysis was conducted using content analysis. Results Twenty-nine references were included, and 30 surveillance systems were identified and classified into general health behaviour surveillance (n = 15) and specific systems for suicide and self-harm (n = 15). General health behaviour systems often operate at national data collection level, collecting non-fatal data in healthcare settings, mainly emergency departments. The specific systems exhibited greater variability in terms of context, involved actors, data collection level, data collection procedures, and case classification. Limitations found by the studies pointed mostly to case definitions and data quality. Co-production, intersectoral collaboration, clear case definition criteria and data standardisation are essential to improve surveillance systems for suicide and self-harm. Conclusions This review identified the characteristics of surveillance systems for suicide and self-harm. Monitoring and evaluation are crucial for ongoing relevance and impact on prevention efforts.